Properties of Weakly $β(Λ,p)$-open Functions and Weakly $β(Λ,p)$-closed Functions (European Journal of Pure and Applied Mathematics, 2024)
This paper deals with the concepts of weakly β(Λ, p)-open functions and weakly β(Λ, p)-closed functions. Moreover, some properties of weakly β(Λ, p)-open functions and weakly β(Λ, p)-closed functions are investigated.
Keywords: weakly $β(Λ,p)$-open functions; weakly $β(Λ,p)$-closed function